Orthopedic Surgery <50 Days Following Covid-19 Infection Is Not Associated With Increased Postoperative Complications - Koschmeder, Katelyn T; Driscoll, J Adam; Hartog, Taylor Den; Halbur, Christopher; Bailey, Ryan; Kuperman, Ethan; Patterson, Brendan M; Olinger, Catherine; Noiseux, Nicolas O (The Iowa orthopaedic journal, 2024)
Recent literature indicates that COVID-19 infection is a negative predictor of good outcomes following elective orthopedic surgery. However, the ideal timing of surgery after infection is unclear. The purpose of this study was to compare the rates of post-operative complications between those who underwent elective orthopedic surgery <50 days and >50 days after COVID-19 infection. This is a pilot study utilizing retrospective review of 28 adult subjects who underwent orthopedic surgery including 17 total-knee arthroplasties, seven total-hip arthroplasties, three posterior spinal fusions, and one common peroneal decompression. These subjects were indicated for an orthopedic surgery that was canceled due to positive pre-operative COVID-19 testing. The subjects were rescheduled for surgery between March 2020-December 2022.There were two cohorts: those who underwent surgery <50 days after COVID-19 infection (n=14) and subjects who underwent surgery >50 days after COVID-19 infection (n=14). Demographics, preoperative comorbid conditions, and post-operative complications were recorded and compared. There were no significant demographic differences between the two cohorts with respect to age, body mass index, weight, and American Society of Anesthesiologists (ASA) grade. The two cohorts had no significant difference in pre-existing comorbid conditions with hypertension and peripheral vascular disease being the most common comorbidities overall. There were six postoperative complications involving four subjects within 90 days of surgery. One subject developed a postoperative pulmonary embolism (PE), and another subject developed a surgical-site infection, sepsis, and renal failure; both in the >50 days cohort. One patient in each cohort required reoperation. There was no difference in postoperative complications such as deep vein thrombosis (DVT), PE, sepsis, renal failure, and intensive care unit (ICU) admission between the two cohorts. This pilot cohort study demonstrates that COVID-19 infection within 50 days of orthopedic surgery does not significantly increase the risk of postoperative complications such as DVT, PE, surgical site infection, renal failure, ICU admission, reoperation, or death. Further evaluation of the effects of COVID-19 on surgical outcomes in larger cohorts is warranted. .